1998
DOI: 10.1002/(sici)1098-108x(199809)24:2<207::aid-eat10>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders among female adolescents in Switzerland: Prevalence and associations with mental and behavioral disorders

Abstract: Objectives: To measure the prevalence of eating disorders in a national representative sample of adolescent girls and association of eating disorders with other behavioral/mental problems in Switzerland. Methods: As part of a national health survey, a subsample of 1,084 15 to 20‐year‐old female students attending school aged filled in a self‐administered anonymous questionnaire focusing on eating behavior and body image. Factor analysis made on these specific questions reveals two major dimensions: weight and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 16 publications
2
8
0
4
Order By: Relevance
“…Comparing our results with those reported in similar populations elsewhere, the percentage of female athletes who vomit frequently (3.5 %) is similar to the figure of 4 % reported in the US by Roberts et al [27], but lower than the figures found by Johnson et al [16] (6.41 %) and Sundgot-Borgen in Norway [12] (10%), though the latter's screening study reported the rate to be 3 %. The proportion of Spanish athletes who diet (24 %) was between the figures of 11 % and 50 % recorded in other studies [27]. The use of laxatives in our sample was very similar to that observed in US athletes (1.1 % versus 1.78 %) [27].…”
Section: Eating Disorders Symptomatologysupporting
confidence: 89%
“…Comparing our results with those reported in similar populations elsewhere, the percentage of female athletes who vomit frequently (3.5 %) is similar to the figure of 4 % reported in the US by Roberts et al [27], but lower than the figures found by Johnson et al [16] (6.41 %) and Sundgot-Borgen in Norway [12] (10%), though the latter's screening study reported the rate to be 3 %. The proportion of Spanish athletes who diet (24 %) was between the figures of 11 % and 50 % recorded in other studies [27]. The use of laxatives in our sample was very similar to that observed in US athletes (1.1 % versus 1.78 %) [27].…”
Section: Eating Disorders Symptomatologysupporting
confidence: 89%
“…For example, prior work has shown an elevated rate of suicide attempts in adolescents with behaviors such as binge eating and purging. [4][5][6][7][8] The relationship between suicidal behavior and less severe weight control behaviors has not been defined. Similarly, the relationship, if any, between body dissatisfaction and suicidal behavior has received very little attention.…”
Section: Introductionmentioning
confidence: 99%
“…La especificidad inferior a la esperada podría explicarse por la popularización de las conductas relacionadas con reducción del peso en mujeres jóvenes pero no en mujeres mayores (33,34). Esto explicaría la mayor especificidad encontrada en el estudio de Luck quien, como ya se mencionó, incluyó mujeres de 18 a 50 años (20).…”
Section: Discussionunclassified